Philosophy behind Islamic Economics: Limited Desires and Unlimited Resources - Malik Shahzad Shabbir; Husnain Ahmed (Global Review of Islamic Economics and Business, 2020)
The most famous definition of economics among modern academicians and economists is a branch of science which deals with the study of the relationship between limited resources and unlimited wants or desires. Under the shadow of this definition, there are different types of conventional economic systems included relativism, utilitarianism, and universalism, etc. This study has been introduced in the economic world through an evolution process. There is a dominant feeling within the Muslim elites that either Islam is unable to respond to complex contemporary challenges in the fields of trade and economics or its economic concepts are old and outdated. Both of these perceptions are incorrect. The real philosophy, concept, and definition of Islamic economics are based on limiting desires and unlimited resources which are supported by Quran and Hadith. The beauty of Islamic economics is based on limited desires and unlimited resources. This concept of Islamic economics can share the risk of profit and loss in their business. Islamic banks with this revolutionary approach will feel at ease in implementing Shari’ah-based finance and offer risk-sharing products and services.